2006
DOI: 10.1021/es0604360
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Determined Uranium Isotope Fractionation During Reduction of Hexavalent U by Bacteria and Zero Valent Iron

Abstract: Variations in stable isotope ratios of redox sensitive elements are often used to understand redox processes occurring near the Earth's surface. Presented here are measurements of mass-dependent U isotope fractionation induced by U(VI) reduction by zerovalent iron (Fe0) and bacteria under controlled pH and HCO3- conditions. In abiotic experiments, Fe0 reduced U(VI), but the reaction failed to induce an analytically significant isotopic fractionation. Bacterial reduction experiments using Geobacter sulfurreduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 44 publications
3
57
3
1
Order By: Relevance
“…The lack of isotope fractionation for sulfide-or organic-mediated reduction may be attributed to direct two-electron transfer from organic matter or S 2− to U(VI), resulting in the sequestration of U(IV) and a strongly unidirectional reaction with insignificant isotope fractionation. The same lack of fractionation was observed in two other studies using reducing agents that operate via twoelectron transfer: zerovalent iron by which Fe(0) transfers two electrons to U(VI) to form Fe(II) and U(IV) (34) and zerovalent zinc by which Zn 2+ and U(IV) are produced (9).…”
Section: Discussionsupporting
confidence: 71%
“…The lack of isotope fractionation for sulfide-or organic-mediated reduction may be attributed to direct two-electron transfer from organic matter or S 2− to U(VI), resulting in the sequestration of U(IV) and a strongly unidirectional reaction with insignificant isotope fractionation. The same lack of fractionation was observed in two other studies using reducing agents that operate via twoelectron transfer: zerovalent iron by which Fe(0) transfers two electrons to U(VI) to form Fe(II) and U(IV) (34) and zerovalent zinc by which Zn 2+ and U(IV) are produced (9).…”
Section: Discussionsupporting
confidence: 71%
“…At the same time, the sulfate and sulfide concentrations in M-24 also dropped, but the decrease in sulfate was not as pronounced as in M-21. The small fractionation between the δ 34 S values of sulfate and sulfide (to <2‰) in these wells during this time period is a clear indication of sulfate limitation (17,21). This is also the time period during which the U(VI) concentrations rebounded to near background levels (Figure 2h).…”
Section: Resultsmentioning
confidence: 72%
“…Recent studies have also demonstrated enrichment of 238 U relative to 235 U in residual U(VI) during microbial uranium reduction (21). However, the use of sulfur isotopes as indicators of bioremediation progress has been limited to laboratory experiments and nonamended field-scale studies (22).…”
Section: Introductionmentioning
confidence: 99%
“…Rademacher et al [35] investigated the process of uranium(VI) removal by Fe 0 by means of isotope fractionation and reported that "Fe 0 reduced U VI , but the reaction failed to induce an analytically significant isotopic fractionation". This obviously questionable conclusion was consistent with the MTW concept and the results of Gu et al [36] Jia et al [12] investigated the adsorption of triazoles by iron hydroxides/oxides (Fe 2 O 3 , ferrihydrites) and elemental iron.…”
Section: Experimental Observationsmentioning
confidence: 99%